1991
DOI: 10.1017/s0003356100012848
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of phase feeding and choice feeding as methods of meeting the amino acid requirements of growing pigs

Abstract: Two experiments are reported in which a comparison was made of phase feeding and choice feeding as methods of meeting the changing amino acid requirements of growing pigs. In the first experiment, three feeding strategies were used: a system in which a single food (165 g protein per kg food) was offered throughout the growth period; a phase-feeding system, using five different treatments; and three choice-feeding treatments, in which the two diets offered differed only in their protein concentrations. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…It was reported that individually housed pigs can differentiate between diets of different proteiq levels and tend to select a protein intake to meet their requirements (Kyriazakis, 1989;Kyriazakis et al, 1990). These observations were supported by the results of Bradford and Gous (1991), who also suggested that choice feeding appears to have greater potential for commercial swine operations than does phase feeding.…”
Section: The Need Of Application Of Phase Feedingsupporting
confidence: 54%
See 1 more Smart Citation
“…It was reported that individually housed pigs can differentiate between diets of different proteiq levels and tend to select a protein intake to meet their requirements (Kyriazakis, 1989;Kyriazakis et al, 1990). These observations were supported by the results of Bradford and Gous (1991), who also suggested that choice feeding appears to have greater potential for commercial swine operations than does phase feeding.…”
Section: The Need Of Application Of Phase Feedingsupporting
confidence: 54%
“…Dourmad et al (1996) reported that the requirement for true digestible lysine decreased from about 0.80gMJ in NE at 50 kg to 0.63 glMJ at 100 kg live weight. Bradford and Gous (1991) reported that there was an improvement in the efficiency of feed utilization and a reduction in feed intake of growing-finishing pigs (25-90 kg) as the number of phases was increased from one (the control) to five.…”
Section: Effects Of Phase Feeding Regimen On Growth Performancementioning
confidence: 99%
“…Based on those studies, which were mainly conducted with diets varying in their overall protein content, several authors (Kyriazakis et al, 1990, Bradford andGous, 1991b;Rose and Kyriazakis, 1991) considered a choice feeding system to be an alternative to common feeding strategies with possible economic and ecologic advantages in commercial pig production. Moreover, because diet selection for nutrients seems sometimes very precisely related to the animals' requirements, Livestock Science 122 (2009) [259][260][261][262][263] choice feeding studies have also been discussed as a possibility to estimate nutrient requirements in farm animals (Kirchgessner and Paulicks, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…(Kyriazakis 1989;Kyriazakis et al 1990). These observations were supported by the resulS of Bradford and Gous (1991b), who also suggested that choice feeding appears to have more potential for commercial swine operations than does phase feeding. In contrast, Owen et al (1994) reported ttrat growing-finishing pigs do not have the ability to selert the correct proportions of each diet to optimize performance and carcass leanness when offered a choicebf lowand highJysine sorghum-soybean meal diets.…”
mentioning
confidence: 64%